Motives for millennials' choice on traditional food and their level of consumption: A cross-cultural comparison. - Tan, Ai Ling *; Yow, Taw Onn (2016)
Malaysian cuisine is known for its vibrant and diverse flavours which reflects the multi-ethnic makeup of its population. Hence, it is interesting to investigate how the differences of background and cultures lead to different food consumption and motives for food choices among different ethnic groups. This study aims to investigate the relationship between consumption of traditional food and motives for food choice among millennial in Malaysia with ethnicity as the moderator. A self-administered questionnaire was distributed to 922 representative millennial which consisted of Malays (31%), Chinese (35.9%) and Indians (33.1%). The results of this study indicate that health concern, familiarity, mood and ethical concerns significantly influence the millennials’ general attitude towards traditional food consumption. Additionally, PLS-Multi-Group Analysis (MGA) was employed to study the association of food choice motives, general attitude and the level of consumption among the young Malays, Chinese and Indians in Malaysia. The results show that the differences in background and cultures between Malays and Chinese, and Malays and Indians, moderate the effect of mood on the general attitude towards traditional food. While for Chinese and Indians, different background and cultures moderate the influence of convenience on the general attitude towards traditional food.